Understanding poverty and well-being in Mozambique: the first national assessment, 1996-97 - Ministry of Planning and Finance, Government of Mozambique; Eduardo Mondlane University; International Food Policy Research Institute (Ministry of Planning and Finance, Government of Mozambique, 1998)
The report Understanding Poverty and Well-Being in Mozambique: The First National Assessment (1996-97) has grown out of an almost three-year long collaborative research effort between the International Food Policy Research Institute (IFPRI), the Department of Population and Social Development (DPDS, previously the Poverty Alleviation Unit) in the National Directorate of Planning and Budget at the Ministry of Planning and Finance, and the Faculty of Agronomy and Forest Engineering at Eduardo Mondlane University (UEM). Mozambique is at a unique juncture in its path of economic development. With peace since 1992 has come both the opportunity and challenge of development. The recent growth experience is testimony to the opportunity for future economic progress, while the critical challenge for the country is to ensure that the poor participate in and benefit at least proportionately, and one hopes more than proportionately, from the emerging growth process. This challenge also has a political dimension: broader participation in the benefits of economic growth will also enhance the prospects for sustained peace and stability.